2018
DOI: 10.1111/anae.14143
|View full text |Cite
|
Sign up to set email alerts
|

Adverse drug reactions

Abstract: SummaryAdverse drug reactions are a cause of significant morbidity and mortality to patients and a source of financial burden to the healthcare system. Of the wide spectrum of adverse drug reactions, the most concerning to the anaesthetist remain anaphylaxis and malignant hyperthermia. Although the incidence of anaphylaxis under anaesthesia is difficult to ascertain, it occurs commonly enough that most anaesthetists will manage at least one case in their career. The wide range of drugs given in the peri-operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(44 citation statements)
references
References 43 publications
0
35
0
1
Order By: Relevance
“…We found that some aspects of anaphylaxis to intravenous gelatin‐based solutions followed the typical clinical features of peri‐operative anaphylaxis . As in NAP6, the commonest presenting sign was hypotension and, consistent with peri‐operative anaphylaxis, reactions were severe.…”
Section: Discussionmentioning
confidence: 60%
“…We found that some aspects of anaphylaxis to intravenous gelatin‐based solutions followed the typical clinical features of peri‐operative anaphylaxis . As in NAP6, the commonest presenting sign was hypotension and, consistent with peri‐operative anaphylaxis, reactions were severe.…”
Section: Discussionmentioning
confidence: 60%
“…ADRs cause a lot of suffering to the patient with considerable mortality and morbidity, as well as an increase in medical care expenses. Its importance becomes greater in relation to the current increase in the use of drugs, polypharmacy and multimorbidity [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Adverse drug reactions are historically classified into two main categories, which describe a general mechanistic distinction (1,2). Type A reactions are common and their effects are predictable and mostly dose-dependent.…”
Section: Introductionmentioning
confidence: 99%